2016
DOI: 10.1523/jneurosci.0554-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Infection Determines the Localization of Damage and Extent of Sensorineural Hearing Loss in Experimental Pneumococcal Meningitis

Abstract: Hearing loss is an important sequela of pneumococcal meningitis (PM), occurring in up to 30% of survivors. The role of the severity of infection on hearing function and pathomorphological consequences in the cochlea secondary to PM have not been investigated to date. Using a well-established model of PM, we systematically investigated the functional hearing outcome and the long-term fate of neurosensory cells in the cochlea, i.e., hair cells and spiral ganglion neurons (SGNs), with a focus on their tonotopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 45 publications
7
64
0
1
Order By: Relevance
“…Different studies have demonstrated the location of new bone formation in TB with labyrinthitis ossificans . Our findings are consistent with other studies that showed the presence of new bone formation beginning at the lower segments of the cochlea . We were able to find new bone formation (close the RWM or throughout the cochlea) in two (13.3%) TBs.…”
Section: Discussionsupporting
confidence: 92%
“…Different studies have demonstrated the location of new bone formation in TB with labyrinthitis ossificans . Our findings are consistent with other studies that showed the presence of new bone formation beginning at the lower segments of the cochlea . We were able to find new bone formation (close the RWM or throughout the cochlea) in two (13.3%) TBs.…”
Section: Discussionsupporting
confidence: 92%
“…Inflammatory mediators (cytokines, chemokines, reactive oxygen and nitrogen species, MMPs) released from recruited neutrophils, endothelial cells, leptomeningeal macrophages and brain-resident microglia and astrocytes contribute to pathogen eradication but also act as neurotoxins and induce neuronal damage [107,116,119,120]. Moreover, PM induces damage to hair cells and spiral ganglion neurons in the inner ear [121][122][123] provoking sensorineural hearing impairments in up to 30% of survivors [108,124,125]. In an infant rat PM model, increased CSF levels of TNF-α during acute infection were positively correlated with increased hearing loss in surviving animals [122].…”
Section: Pathophysiology Of Brain Injury During Bacterial Meningitismentioning
confidence: 99%
“…Moreover, PM induces damage to hair cells and spiral ganglion neurons in the inner ear [121][122][123] provoking sensorineural hearing impairments in up to 30% of survivors [108,124,125]. In an infant rat PM model, increased CSF levels of TNF-α during acute infection were positively correlated with increased hearing loss in surviving animals [122].…”
Section: Pathophysiology Of Brain Injury During Bacterial Meningitismentioning
confidence: 99%
See 2 more Smart Citations